Different antiviral effects of IFNα subtypes in a mouse model of HBV infection - Jingjiao Song (Nature Portfolio, 2017)
Abstract Interferon alpha (IFNα) is commonly used for the treatment of chronic hepatitis B (CHB) patients. There are 13 different IFNα subtypes in humans, but only the subtype IFNα2 is used for clinical treatment. The antiviral activities of all other IFNα subtypes against HBV have not been studied. To obtain basic knowledge about the direct antiviral as well as the immunomodulatory effects of IFNα subtypes, we used the HBV hydrodynamic injection (HI) mouse model. Application of most IFNα subtype proteins inhibited HBV replication in vivo, with IFNα4 and IFNα5 being the most effective subtypes. Decreased viral loads after therapeutic application of IFNα4 and IFNα5 correlated with expanded effector cell populations of NK cells and T cells in both liver and spleen. Hydrodynamic injection of plasmids encoding for the effective IFNα subtypes (pIFNα) was even more potent against HBV than injecting IFNα proteins. The combination of pIFNα4 and pIFNα5 showed a synergistic antiviral effect on HBV replication, with a strong increase in NK cell and T cell activity. The results demonstrate distinct anti-HBV effects of different IFNα subtypes against HBV in the mouse model, which may be relevant for new therapeutic approaches.